ANALISIS PERHITUNGAN HARGA POKOK PESANAN (JOB ORDER COSITING) PADA CV ARINDA MOULDING DI SAMARINDA - PRAMITA SUSANTY; NURITA AFFAN; FIBRIANI NUR KHAIRIN (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
For industrial company owner specially manufacture in fundamental price pix produce pursuant to cost of good sold the order of vital importance, because representing one of base for pricing sell and advantage yielded by earn bigger. internal issue Formula this research  how calculation of job order costing at CV Arinda Molding in Samarinda. Intention of this research is to analyze and know the level of job order costing yielded by company at CV Arinda Molding in Samarinda. The data obtained in this study is by using the following technique : Field Work research that is directly came out on the object of study as observation and documentation. Observation, is observe directly the object under study in order to obtain the required data. Documentation, concluded the necessary documents to support the research. Library research that is by way of collecting data related to the research that comes from the literatures or other writings. Analyze used in this research is calculate the factory overhead cost determined in the face of, calculation job order costing and make the fundamental price tag. Method analyze in conducting this examination, researcher use the comparability method. Comparability method that is method analyze by comparing between calculation of job order costing applied by company at CV Arinda Molding with calculation job order costing by theory  cost accounting. Pursuant to research result show: existence of calculation difference conducted by company at CV Arinda Molding pursuant to job order costing theory order by cost accounting. This difference is happened  because calculation method the according to report at CV Arinda Molding very traditional, that is do not count the cost the factory overhead, all expense released only classification into permanent material cost and labor cost and also do not make the fundamental price tag. While in calculation production cost there is three expense element which must be used  that is permanent material cost, direct labor cost  and factory overhead cost determined in the face and also make the fundamental price tag. Others, CV Arinda require to conduct the record-keeping or bookkeeping in each transaction that happened. Inferential so that that calculation job order costing at CV Arinda Molding in Samarinda not yet as according to theory by cost accounting  about job order costingKeyword: Cost Accounting, Factory Overhead Cost, JOB Order Costing.